Disinfection by-Products and Ecotoxic Risk Associated with Hypochlorite Treatment of Tramadol - Valeria Romanucci; Antonietta Siciliano; Emilia Galdiero; Marco Guida; Giovanni Luongo; Renato Liguori; Giovanni Di Fabio; Lucio Previtera; Armando Zarrelli (Molecules, 2019)
In recent years, many studies have highlighted the consistent finding of tramadol (TRA) in the effluents from wastewater treatment plants (WTPs) and also in some rivers and lakes in both Europe and North America, suggesting that TRA is removed by no more than 36% by specific disinfection treatments. The extensive use of this drug has led to environmental pollution of both water and soil, up to its detection in growing plants. In order to expand the knowledge about TRA toxicity as well as the nature of its disinfection by-products (DBPs), a simulation of the waste treatment chlorination step has been reported herein. In particular, we found seven new by-products, that together with TRA, have been assayed on different living organisms (Aliivibrio fischeri, Raphidocelis subcapitata and Daphnia magna), to test their acute and chronic toxicity. The results reported that TRA may be classified as a harmful compound to some aquatic organisms whereas its chlorinated product mixture showed no effects on any of the organisms tested. All data suggest however that TRA chlorination treatment produces a variety of DBPs which can be more harmful than TRA and a risk for the aquatic environment and human health.